1971
DOI: 10.1017/s0014479700004919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry Organic Matter on Growth and Yield of Beans (Phaseolus vulgaris L.)

Abstract: Incorporation of dry matter of perennial soybean into the soil, alone or with mineral fertilization, resulted in improved vegetative growth of common beans. Fairly high LAI was observed at flowering time where dry organic matter had been added, causing leaf self-shading and decreased growth in the later states of development. In contrast, both the control and mineral fertilized plots showed slower but continuous growth up to 50 days from plant emergence. Only slight differences in grain yield were noticed desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Generally, plants grew much more vigorously and had faster ground cover with increasing N. LAI and total DM were highest at 120 kgjha N and 160 kgjha N, respectively, thereafter, there was a decline. Magalhaes, Montojos and Miyasaka (1971) reported that the addition of 25 metric tonsjha of dry organic matter plus 20 kgjha N reduced LAI, crop growth ~ate (C<? 'R), and net assimilation rate (NAR) in mdetermmate beans after flowering compared to treatments which received lower nutrient levels which increased LAI, CGR and NAR afte; flowering: They attributed reduction in CGR and NAR to self-shading that occurred when LAI was around or abov(: 3.0.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, plants grew much more vigorously and had faster ground cover with increasing N. LAI and total DM were highest at 120 kgjha N and 160 kgjha N, respectively, thereafter, there was a decline. Magalhaes, Montojos and Miyasaka (1971) reported that the addition of 25 metric tonsjha of dry organic matter plus 20 kgjha N reduced LAI, crop growth ~ate (C<? 'R), and net assimilation rate (NAR) in mdetermmate beans after flowering compared to treatments which received lower nutrient levels which increased LAI, CGR and NAR afte; flowering: They attributed reduction in CGR and NAR to self-shading that occurred when LAI was around or abov(: 3.0.…”
Section: Discussionmentioning
confidence: 99%
“…The productivity of common bean crops appeared compromised in organic cultivation systems [118,120], where the timing of N supply is remarkably challenging because the mineralisation rates of organic manures is weather-and soil-dependent. In contrast, no significant variations in yield of common bean were found in organic or inorganic fertigation managements in the studies of Uyanoz [121], Karunji et al [122], and Magalhaes et al [123]. Karunji et al [122] reported that the effects of organic fertilizers on soils and plants are detectable in a long run because the differences in yield were significant in the second and third season of cultivation.…”
Section: Fertilizationmentioning
confidence: 94%
“…The soil properties should be taken into account prior to crop establishment and application of a specific fertilization scheme. According to Magalhaes et al [123], the different farming systems (organic vs. conventional) do not influence the yield when the crop is established in infertile soil with good crop-nutritional provisions. Application of more-complex organic or naturally occurring N source alternatives to chemical fertilizers, which improve soil fertility, function, and resilience, should also be considered as a restorative fertilization management practice.…”
Section: Fertilizationmentioning
confidence: 99%
“…Yield of seed per plant (823 g at 10% water content) indicates the high yield potential of this genotype when planted at a density of 1 plant/m 2 . Although the growth period is long compared with bush varieties planted in the tropics (Magalhaes et al, 1971;Wien et al, 1973;Aguilar-Mariscal et al, 1977) the average yield of seed/plant/day (4.9 g m~2 day" 1 ) exceeds the average yield recorded by CIAT (1976) of 3.7, 3.2, 3.4 g m" 2 day" 1 for the outstanding bush varieties, and compares favourably with Type IV cv P-589 (4.7 g m" 2 day" 1 ), with a growing period of 96 days.…”
Section: Resultsmentioning
confidence: 99%